Application of Ex Officio Rights Based on Gender Justice in Divorce Lawsuit in Surabaya Religious Court, Indonesia - Azizah; Ali Hisyam, Mohammad; Abou-Bakr, Omaima (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The divorce rate of PA Surabaya in 2022 was recorded at 10,327 divorce applications, 5,802 cases were decided, 4,171 divorce cases compared to 1,631 cases. High number of divorce cases makes PA Surabaya must play role and be able to resolve Islamic family law problems fairly for the litigants. This research is text-based through the reading of court rulings from gender justice perspective. The purpose of the study: (1) to know the legal basis for the judge's consideration in the divorce lawsuit case Number:3950/Pdt.G/2023/PA.Sby. (2) How to apply Ex Officio rights based on gender justice in PA Surabaya for the fulfillment of wife's rights after divorce. The type of qualitative research is in the form of analysis of divorce case decisions, in-depth interviews, with judges who tried cases number (3950/Pdt.G/2023/PA.Sby). Using a gender approach with benefit indicators, not based on stereotypes (ridicule), don’t lead to the creation of marginalization (sex differentiation), don’t lead to gender-based violence and the absence of subordination (deviation of one gender). The results of this study show that PA Surabaya in legal products, especially in divorce lawsuits, is not accordance with the principles of gender justice, able to equalize gender by punishing husbands to pay muth'ah, iddah, hadhonah to ex-wives even though it’s not written in the lawsuit with Ex Officio rights and cooperates with the Surabaya City Government for the implementation of decisions and as a pioneer in the implementation of Book II article 41 C of Law Number 1 of 1974 and PERMA No.3 Year 2017.